2014
DOI: 10.1111/1365-2435.12294
|View full text |Cite
|
Sign up to set email alerts
|

Costly sexual dimorphism in Cyclommatus metallifer stag beetles

Abstract: Summary1. In many animal species, male armature has evolved through sexual selection. This male weaponry can increase reproductive success, but only if the owner overcomes the associated costs. 2. Male stag beetles bear one of the most extreme examples of male weaponry: their mandibles can be almost as long as their own body. We question whether the armature of male Cyclommatus metallifer negatively affects terrestrial locomotion (stability and cost). If so, we investigate whether these effects are potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 39 publications
0
58
1
Order By: Relevance
“…The advantages of bearing enlarged weapons becomes particularly evident during stag beetles male-male interaction, giving an enhanced capacity for dislodging the opponent, both in interspecific and intraspecific contests (Hongo andOkamoto 2013, Lagarde et al 2005), thus shortening the battle duration (Goyens et al 2015a) and finally resulting in increased mating opportunities. However, exaggerated mandibles can be costly in terms of impairing locomotion and stability (Goyens et al 2015b) and constraining flight ability (Goyens et al 2015c). Despite the great investment in SSC by major males, Romiti et al (2016) suggested that functional constraints, (for example, enhanced mechanical stress and reduced flight performance), may have shaped the mandibles of larger L. cervus males.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of bearing enlarged weapons becomes particularly evident during stag beetles male-male interaction, giving an enhanced capacity for dislodging the opponent, both in interspecific and intraspecific contests (Hongo andOkamoto 2013, Lagarde et al 2005), thus shortening the battle duration (Goyens et al 2015a) and finally resulting in increased mating opportunities. However, exaggerated mandibles can be costly in terms of impairing locomotion and stability (Goyens et al 2015b) and constraining flight ability (Goyens et al 2015c). Despite the great investment in SSC by major males, Romiti et al (2016) suggested that functional constraints, (for example, enhanced mechanical stress and reduced flight performance), may have shaped the mandibles of larger L. cervus males.…”
Section: Discussionmentioning
confidence: 99%
“…However, females (as a proxy for the hypothetical non-dimorphic male; cf. [10,11]) bite 66% less forcefully than males do at the medial protrusions (even after size-normalization, [10]). Therefore, male tip biting may still be considered 'forceful' biting, yet limited due to trade-offs between structural weight and locomotion.…”
Section: Finite-element Model: Bite Force Modulationmentioning
confidence: 93%
“…The equilibrating external forces and moments needed to maintain this steady state can derive only from the wings and must be considered as the net effect (in terms of forces and moment transfer) from the wings to the body as averaged over a wing beat cycle. These net forces and moments apply on the rigid body almost vertically above the experimentally determined position of the body centre of mass [10]. Horizontal and vertical forces (wing, aerodynamic and gravity) must cancel each other out to proceed in a steady horizontal manner (figure 2).…”
Section: Force Balancementioning
confidence: 99%
“…The non-dimorph state is represented by the scaled female morphology, because the male and female morphology is very alike in stag beetle species without sexual dimorphism [10,22] ( figures 1 and 4a,c,d). The non-dimorph model was scaled in such a way that the posterior body part (meso-and metathorax þ abdomen) was as large as in the complete model [10]. For both the without mandibles and non-dimorph model, the total mass was reduced to conform to our weight measurements (on fresh material with an analytical microbalance; MT5; Mettler Toledo, Columbus, OH; precision: 5 mg; table 1), and the position of the centre of mass was adapted according to the altered model volume.…”
Section: Simulation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation